Unconventional apoptosis of polymorphonuclear neutrophils (PMN): staurosporine delays exposure of phosphatidylserine and prevents phagocytosis by MΦ-2 macrophages of PMN. (26th November 2014) - Franz, S; Muñoz, L E; Heyder, P; Herrmann, M; Schiller, M
Summary: Apoptosis of polymorphonuclear neutrophils (PMN) and subsequent 'silent' removal represents an important check-point for the resolution of inflammation. Failure in PMN clearance resulting in secondary necrosis-driven tissue damage has been implicated in conditions of chronic inflammation and autoimmunity. Apoptotic PMN undergo profound biophysical changes that warrant their efficient recognition and uptake by phagocytes before fading to secondary necrosis. In this study, we demonstrate that staurosporine (STS), a non-selective but potent inhibitor of cyclin-dependent kinase and protein kinase C, exerts a drastic impact on PMN apoptosis. PMN treated with STS underwent an unconventional form of cell death characterized by a delayed exposure of aminophospholipids, including phosphatidylserine (PS) and phosphatidylethanolamine and an increased exposure of neo-glycans. STS caused an impaired cellular fragmentation and accelerated DNA fragmentation. Phagocytosis of STS-treated PMN lacking PS on their surfaces was decreased significantly, which highlights the importance of PS for the clearance of apoptotic PMN. Specific opsonization with immune complexes completely restored phagocytosis of STS-treated PMN, demonstrating the efficiency of back-up clearance pathways in the absence of PS exposure.